2016
DOI: 10.1002/jrs.5042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C70 rotation on the photoluminescence spectra of compressed C70*mesitylene

Abstract: The efficient photoluminescence (PL) emission of solvated fullerenes has attracted significant interest because of their potential applications. Uncovering the possible factors that govern the PL emission of solvated fullerenes thus becomes important for the purpose of application. Here, we report a high pressure study on a typical solvated fullerene, C70*mesitylene, using the diamond anvil cell technique with associated spectroscopic measurements. Our Raman and PL spectra show that there is a change in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(85 reference statements)
2
5
0
Order By: Relevance
“…While the observed PL originates from the transition of the first excited singlet state S1 to the ground state S0, the slow decay process observed for the C60 nanowires is understood to arise from a weakly allowed intramolecular transition and/or interactions between the C60 and m-xylene molecules present in the nanowire structure. 52 Similar lifetime values were observed by Byrne et al 53 and Jie et al 54 for C60 single crystals and films, respectively.…”
Section: Morphology and Microstructuresupporting
confidence: 78%
“…While the observed PL originates from the transition of the first excited singlet state S1 to the ground state S0, the slow decay process observed for the C60 nanowires is understood to arise from a weakly allowed intramolecular transition and/or interactions between the C60 and m-xylene molecules present in the nanowire structure. 52 Similar lifetime values were observed by Byrne et al 53 and Jie et al 54 for C60 single crystals and films, respectively.…”
Section: Morphology and Microstructuresupporting
confidence: 78%
“…Their Raman and PL spectra show that there is a change in the pressure dependence for the normalized PL intensity in solvated samples during the rotational transition. It indicates that the rotational state of C 70 is a critical factor, which can influence the PL emission of solvated samples . Goryainov et al carried out an in‐situ Raman study of phengite compressed in water medium under simultaneously high P–T parameters.…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%
“…In previous studies, phase transitions, polymerizations, and amorphizations were observed when high pressure treatments were carried out on fullerene materials [23][24][25]. Accompanied with the structural changes induced by pressure, new physical and chemical properties have occurred on fullerene [26,27]. Notably, recent high pressure studies have shown that fullerene solvates exhibit unusual compression behaviors and can transform into novel phases.…”
Section: Introductionmentioning
confidence: 99%